Dye-sensitized solar cells : mathematical modeling, and materials design and optimization - Soroush, Masoud; Lau, Kenneth K. S., 1972- (Academic Press, an imprint of Elsevier, 2019)
Dye-Sensitized Solar Cells: Mathematical Modelling and Materials Design and Optimization presents the latest information as edited from leaders in the field. It covers advances in DSSC design, fabrication and mathematical modelling and optimization, providing a comprehensive coverage of various DSSC advances that includes different system scales, from electronic to macroscopic level, and a consolidation of the results with fundamentals. The book is extremely useful as a monograph for graduate students and researchers, but is also a comprehensive, general reference on state-of-the-art techniques in modelling, optimization and design of DSSCs.